Information source, information channels and information choice: The mediating effect of personal characteristics - Al - Khateeb, Bilal Ahmad Ali; Md Dahalin, Zulkhairi (2013)
Although a strong relationship has been established between information source, information channels and information choice strategies, however, a mediator is required to further explain why or how the independent variables (information source and information channels) predict the dependents variable (information choice strategy).As a result, the collected data from 358 respondents of Arab tourists in Malaysia was analyzed through the regression analysis.Overall, the findings show significant relationships between information source, information channels and information choice.The result further shows that personal characteristic significantly mediate the relationship between information source, information channels and information choice. Hence, the study concludes that personal characteristic significantly explains the relationship between information source, information channels and information choice. Based on the findings obtained in this study, implications for the study and future research including the limitations are discussed.